Studies associating blastocystis sp. tocolorectal cancer Vinoth s/o Kumarasamy - Kumarasamy, Vinoth (2014)

(untitled)
Cancer has become a vital public health issue around the world. Colorectal cancer (CRC) has become one of the major causes of deaths worldwide. Numerous reports have correlated infectious agents and cancer including CRC. Infectious agents are known to contribute to 20% of CRC. Recent findings have demonstrated the possible correlation between Blastocystis and CRC with many conflicting reports on the question of pathogenicity of different subtypes of Blastocystis. To improve our understanding on the molecular epidemiology of this parasite, we determined the Blastocystis subtypes (STs) and their relative frequency in CRC patients and control groups. Epidemiological studies related to Blastocystis often give poor results due to poor sensitivity of standard methods available to detect Blastocystis genotypes in the stool sample. As such, prevalence study was conducted using colonic washouts collected from CRC patients and healthy individuals. The mean prevalence of Blastocystis infection was significantly higher among CRC patients (n=43, 21.08%) compared to healthy control (n=22, 9.95%, p < 0.01) and subtype 3 was predominant (12.75%) among these individuals. We also investigated immunoglobulin levels in Blastocystis positive patients who were newly diagnosed with CRC as well as those subjected to chemotherapy. We found the high infection in both newly diagnosed CRC patients and chemotherapy patients with the elevation of specific antibodies. One healthy individual who was negative for Blastocystis both by direct microscopy and in in vitro cultures had higher IgM titers (1:1600) and 4 showed low titres of IgG antibody. A total of 11 healthy individuals were positive for IgG. Significant number of healthy individuals showed the presence of IgA with the exception of one individual who showed the presence at low titers. The finding showed the presence of association between immune response to Blastocystis antigen and CRC. In addition, we also evaluated the effect of solubilized antigen isolated from five different subtypes of Blastocystis on colon cancer cells, HCT116 and peripheral blood mononuclear cell (PBMC) proliferation. Evaluation of gene expression of cytokines, nuclear transcription factors and apoptotic genes in colon cancer cell and immune cells in the presence of Blastocystis was carried out. The proliferation analysis and gene expression findings in the present study implicate a possible pathogenic role for subtype 3 Blastocystis. The inhibitory effect was seen to be higher in PBMCs isolated from CRC patients compared to healthy volunteers which suggests that Blastocystis infection may prevent immune cell propagation to combat the infection. Besides that, the parasite’s influence on the cytotoxic activity of chemotherapy drugs during cancer treatment was also assessed in this study. We designed an in vitro model to specifically analyse the effect of Blastocystis on chemotherapy drug, 5-fluorouracil (5-FU) in colon cancer cells, HCT116 and normal colon fibroblast cells, CCD18-Co. 5-FU caused a dose-dependent increase in the inhibition of cancer cell proliferation. However, the inhibitory effect was reduced in the presence of Blastocystis antigen at 8μM and 10μM of 5-FU. We speculate that Blastocystis antigen could interfere with the efficacy of 5-FU cytotoxicity towards cancer cells. Blastocystis induced expression of inflammatory cytokines, gene transcription factors and angiogenic factors that resulted in resistance of cancer cells against 5-FU. Further validation of the pathogenicity of Blastocystis was carried out using experimental animal models induced with carcinogen, azoxymethane (AOM). Increased crypts formation and increased colorectal dysplasia and elevated level of oxidative damage were observed in the presence of Blastocystis infection. The study underscores the importance of including Blastocystis infection in routine parasitological investigation among CRC patients especially when it can be easily be acquired from contaminated water, food and possibly from animals.